Hubungan Tingkat Hafalan Al-Qur’an dengan Prestasi Akademik Siswa Sekolah Menengah Pertama - Naflah Madaina Arifin; Teguh Hidayat Indaryanto; Puji Lestari; Sri Wahyuningsih (KHD Production, 2024)
The era of globalization must be faced by the entire world of education today. Education has an important role in shaping an individual's character and intellectual abilities. Formal education in Indonesia is often integrated with religious education, one of which is memorizing the Koran. Memorizing the Qur'an (tahfiz) is not only considered an act of worship but is also believed to influence students' academic performance. This research intended to analyze the relationship between the level of memorization of the Al-Qur'an and the academic achievement of class IX students at SMP Al-Ikhlash Lumajang. By integrating memorizing the Qur'an into formal education, it is hoped that this research can provide a better understanding of the benefits and challenges faced. Method used in this research involves collecting data through questionnaires distributed to students, as well as analyzing their academic results. Results bivariate analysis Pearson Correlation shows that there is a positive relationship between the level of memorization of the Al-Qur'an and academic achievement, in semester 1 it was (0.4%), semester 2 (13%), semester 3 (31.8%), and in semester 4 (36.5 %). Conclusion In this research, there is a positive relationship between the level of memorization of the Al-Qur'an and students' academic achievement, which indicates that memorizing the Al-Qur'an can contribute to improving students' learning abilities. Hopefully, this research can provide helpful information for educators and parents to support schools' teaching and learning process.